Analisis Pengaruh Profitabilitas terhadap Harga Saham (Studi Kasus pada Perusahaan Transportasi yang terdaftar di ISSI 2019-2023) - Nurul Inayah; Adellia Ika Maulida (CV. ITTC INDONESIA, 2024)
The aim of this research is to analyze profitability ratios which are based on share price measurements and calculated using return on equity (ROE), net profit margin (NPM), and return on assets. (ROA). All businesses registered with ISSI and operating in the transportation industry between 2019 and 2023 constitute the research population. Seven businesses were observed over five years. using sampling techniques and quantitative research methodology. The two types of data used in this research are quantitative data and secondary data sources which include books, papers and regulations in the form of documents and archives. Return on Equity (ROE), Net Profit Margin (NPM), and Return on Assets (ROA) have no correlation, according to research findings.